1999
DOI: 10.3147/jsfp.34.65
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity of Strains of Flavobacterium columnare from Diseased Fishes.

Abstract: Flavobacterium columnare, the causative agent of "columnaris disease" , is one of the most important bacterial pathogens in freshwater fishes (Wakabayashi, 1993). It was first isolated by Davis in 1922, and named Bacillus columnaris. The organism was variously reclassified as Chondrococcus columnaris (Ordal and Rucker, 1944), Cytophaga columnaris (Garnjobst, 1945) and Flexibacter columnaris (Leadbetter, 1974). The bacterium now belongs to Flavobacterium after Bernardet et al. (1996) amended the description of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
96
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 33 publications
9
96
1
1
Order By: Relevance
“…In contrast to Edwardsiella ictaluri, several studies have indicated distinctive genotypic diversity among F. columnare isolates (Triyanto & Wakabayashi 1999, Arias et al 2004. Despite the genetic polymorphism, primers designed by Welker et al (2005) were able to amplify DNA from all F. columnare fish isolates included in the study by Arias et al (2004) and the 10 F. columnare isolates when used in the m-PCR assay in this study.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast to Edwardsiella ictaluri, several studies have indicated distinctive genotypic diversity among F. columnare isolates (Triyanto & Wakabayashi 1999, Arias et al 2004. Despite the genetic polymorphism, primers designed by Welker et al (2005) were able to amplify DNA from all F. columnare fish isolates included in the study by Arias et al (2004) and the 10 F. columnare isolates when used in the m-PCR assay in this study.…”
Section: Discussionmentioning
confidence: 77%
“…It has a cosmopolitan distribution in temperate and tropical latitudes and has been isolated from an ecologically and phylogenetically diverse spectrum of wild-caught, aquaculture-reared, and ornamental freshwater fishes (Triyanto & Wakabayashi 1999, Schneck & Caslake 2006, Olivares-Fuster et al 2007. Given the nexus of appropriate host and environmental factors, columnaris disease can be economically devastating for the channel catfish Ictalurus punctatus (Rafinesque, 1818) aquaculture industry where in-pond mortality rates among adults and fingerlings can reach 60 and 90%, respectively (Plumb 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitous distribution of the organism in fresh water environments and the tendency for fish to acquire the disease after mechanical and/or environmental insults makes F. columnare among the most described pathogens in cultured, ornamental and wild fish populations (Triyanto and Wakabayashi, 1999;Austin and Austin, 1999;Bader et al, 2003;Jinu and Goodwin, 2004). Epizootics of columnaris are rarely spontaneous and have been troublesome in hatcheries, pen, cage culture and in pond culture, particularly under adverse environmental conditions and factors stressful to the fish.…”
Section: Introductionmentioning
confidence: 99%